2015
DOI: 10.1016/j.plantsci.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Destructuring plant biomass: Focus on fungal and extremophilic cell wall hydrolases

Abstract: The use of plant biomass as feedstock for biomaterial and biofuel production is relevant in the current bio-based economy scenario of valorizing renewable resources. Fungi, which degrade complex and recalcitrant plant polymers, secrete different enzymes that hydrolyze plant cell wall polysaccharides. The present review discusses the current research trends on fungal, as well as extremophilic cell wall hydrolases that can withstand extreme physico-chemical conditions required in efficient industrial processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 122 publications
(164 reference statements)
0
42
0
5
Order By: Relevance
“…Most plant pathogens secrete a complex mixture of hydrolytic enzymes, which enable the pathogens to penetrate and infect the host (Kubicek et al, 2014). These extracellular hydrolytic enzymes are called cell wall-degrading enzymes (CWDEs) (Guerriero et al, 2015;Kikot et al, 2009;Walton, 1994). CWDEs are essential for phytopathogens that do not have specialized penetration structures (Kikot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most plant pathogens secrete a complex mixture of hydrolytic enzymes, which enable the pathogens to penetrate and infect the host (Kubicek et al, 2014). These extracellular hydrolytic enzymes are called cell wall-degrading enzymes (CWDEs) (Guerriero et al, 2015;Kikot et al, 2009;Walton, 1994). CWDEs are essential for phytopathogens that do not have specialized penetration structures (Kikot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Relieving peroxidases of substrate (including H 2 O 2 ) inhibition and product inhibition is essential if efficient degradation of lignin from lignocelluosic biomass is to be achieved in an industrial context . One possible way to overcome substrate and product inhibition of peroxidases is to immobilize enzymes on nano‐magnetic particles that can be easily separated from the reaction products by using a magnet [ and references therein, 82]. The most interesting part of the study was that VP showed synergistic activation when both LiP and MnP were simultaneously and equally active compared to when either MnP or LiP was active alone .…”
Section: Enzymology Of Lignin Degradationmentioning
confidence: 99%
“…Until now, lignin biosynthesis have been recognized in various plant species in particular in transgenic and genetic mutants plants (Table 2). For instance, in Arabidopsis overexpression of CCoAOMT results in enhanced plant height with concomitant increase in lignin compared to control plants [105], In addition, in sorghum four site mutations of COMT, have shown lower levels of lignin and improved biomass digestibility [106], while RNAi silencing of the Pv4CL1 gene in transgenic switchgrass leads to reduced lignin content and improved fermentable sugar yields [107]. Moreover, in sugarcane RNAi suppression of SbCOMT gene reduces lignin content and recalcitrance [108].…”
Section: Lignin Biosynthesis and Degradationmentioning
confidence: 99%